Reverse Engineering to Design an Ergonomic Bio Briquette Packaging Machine - Taufan Maulana Rizaldy; Agus Kusnayat Watnaya; Yusuf Nugroho Doyo Yekti (School of Industrial and System Engineering, Telkom University, 2023)
Briquettes are solids that are produced through the process of compression and pressure application and if burned will produce a small amount of smoke. Briquette production is carried out using a hammer mill where the raw material for briquettes is charcoal which is then crushed into charcoal granules. The packaging process is still done manually using a shovel to fill the 50kg sack and then take it to the sewing machine. The worker's posture when using a shovel has a Rapid Entire Body Assessment (REBA) score of 12 so it has a high work risk of musculoskeletal disorders (MSDs) and requires immediate improvement. The working environment at the company produces pollutants, meaning that there is no capture container for the fall of charcoal grains from the hammer mill. Based on the existing problems, a redesign of the existing machine is needed. The proposed machine was designed using the Reverse Engineering method because the existing condition already uses the machine then the existing machine is decomposed to find out the components and functions of the existing machine to find alternative concepts. The ergonomic approach uses REBA and LBA to determine changes in worker posture and the forces acting in the human spine. The DEM approach was chosen to find out if the charcoal grains dropped from the hammer mill were successfully captured and to find out the flow of the charcoal grains. The results of the proposed machine design have a good impact on workers in the packaging process.